Allosteric Modulation of Cannabinoid Receptor 1—Current Challenges and Future Opportunities - Hryhorowicz, Szymon (Int J Mol Sci, 2019)
The cannabinoid receptor type 1 (CB1R), a G protein-coupled receptor (GPCR), plays an essential role in the control of many physiological processes such as hunger, memory loss, gastrointestinal activity, catalepsy, fear, depression, and chronic pain. Therefore, it is an attractive target for drug discovery to manage pain, neurodegenerative disorders, obesity, and substance abuse. However, the psychoactive adverse effects, generated by CB1R activation in the brain, limit the use of the orthosteric CB1R ligands as drugs. The discovery of CB1R allosteric modulators during the last decade provided new tools to target the CB1R. Moreover, application of the site-directed mutagenesis in combination with advanced physical methods, especially X-ray crystallography and computational modeling, has opened new horizons for understanding the complexity of the structure, function, and activity of cannabinoid receptors. In this paper, we present the latest advances in research on the CB1R, its allosteric modulation and allosteric ligands, and their translational potential. We focused on structural essentials of the cannabinoid 1 receptor- ligand (drug) interactions, as well as modes of CB1R signaling regulation.